Proses Desain Mesin Pengupas Serabut Kelapa Menggunakan Metode Quality Function Development (QFD) Studi Kasus Desa Margarahayu - Tuwandi Juniarto; Zakaria Nur Aziz; Andre Git Git Pamungkas (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Manual stripping of coconut fibers is still widely done by farmers in Margarahayu Village, Muara Telang District, Banyuasin Regency, which causes low work efficiency and high labor requirements. This study aims to design a coconut fiber peeling machine with a Quality Function Deployment (QFD) approach to better suit user needs and be able to increase productivity. This research uses a quantitative approach with instruments such as observation, interviews, questionnaires, documentation, and literature studies. Data analysis techniques were carried out by compiling a House of Quality to determine the priority of consumer attributes and translating them into machine technical specifications. Based on the QFD method, consumers want five main requirement attributes, and the attribute that becomes the top priority in the design process is the ease of use by the operator with a contribution value of 3.873. In addition, the design of this machine is proven to significantly increase productivity when compared to manual or traditional methods that still use wedge tools.